(untitled) - Thomas, Amanda (Cambridge, UK, 2005)
Business Goals is a three-level course in communicative Business English. Each Student's Book provides 30 core hours of class work extendable to over 60 hours using the additional material provided. Functional language, vocabulary and grammar are introduced in manageable amounts. With a focus on listening and speaking, learners are given the opportunity to build their confidence in areas such as telephoning, ordering, networking and dealing with problems in authentic business contexts. The Business Goals Workbooks provide extra practice in all four skills and are also valuable for students preparing for the BEC examinations, with BEC-style activities and exam advice.
Keywords: English language,English language; Business English,Study and teaching,Foreign speakers